ANALISIS KESESUAIAN DAN DAYA DUKUNG KAWASAN WISATA PANTAI LHOKNGA KECAMATAN LHOKNGA KABUPATEN ACEH BESAR Analysist of Suitability and Carrying Capacity of Lhoknga Beach Tourism Lhoknga Subdistrit Aceh Besar District - Taufiq hidayat; Hasan Sitorus; Eka Budiyulianto (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Lhoknga beach is one of the beaches located in the subdistrict of Lhoknga, Aceh Besar District adjacent to Lampuuk beach and can be reached through the way Banda Aceh-Calang. Lhoknga beach is an attraction area for peoples of Banda Aceh, Aceh Besar and other areas that are nearby. This study was conducted in December 2014 to April 2015. Results showed that the water quality parameters in accordance with the quality standards based to Kep-51/MENLH/2004 for tourist activities. Region in Lhoknga Beach as a whole falls into the category of very suitable (S1) indicates the region had not barrier serious to apply the treatment given or only a barrier that did not significantly affect used and would not increase the input / level of treatment given to be used as a beach resort (recreation, swimming, sunbathing, water sports and fishing). The level of carrying capacity in the area of Lhoknga beach was 175 peoples/day or 1.225 peoples /week. The number of visitors who come to the coast about of 136 peoples / week.Keywords : Aceh Besar, Carrying Capacity, Lhoknga Beach, Suitability.